Toluene degradation of biofilm formed by photosynthetic purple bacteria isolated from oil polluted water samples taken at Cau Da port, Khanh Hoa - Thi Minh Nguyet, Nguyen; Thi Lien, Do; Thi Ngoc Mai, Cung; Phuong Ha, Hoang; Thi Nhi Cong, Le (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Toluene is one of the mosttoxic and difficultly degradable aromatic hydrocarbon compounds in nature. Hence, study on approaches to remove toluene is necessary and in hurry. Among methods to degrade toluene, biodegradationby biofilm-forming photosynthetic bacteria is widely carried out. Two photosynthetic bacterial strains, CCĐPy2 and CCĐPy9, which could well degrade toluene and highly form biofilm were isolated from oil polluted water samples at Cau Da Port, Khanh Hoa province. The colonies of strain CCĐPy2 have round, glossy surface,nucleus, convex, yellowish brown, diameterfrom 0.8 to 1.2 mm; and CCĐPy9 colonieshave round, pinkish in color, with sharp edges, diameter from 1 to 2 mm when they were cultured on DSMZ-27 solid medium. The two strains grow well at 30-37 o C, pH 7 and NaCl concentrationof 1.5%. The strain of CCĐPy2 andCCĐPy9 degraded 96.1% and 97.2% toluene with initial concentration of 150 mg/l after 7 day-incubation, respectively. These strains could be contributed to a collection of biofilm-forming photosynthetic bacteria which have capacity of not only toluene degradation but alsoother recalcitrant hydrocarbon removal.